Ide Bunuh Diri pada Remaja; Faktor-Faktor yang Mempengaruhi - Suherman, Amalia Putri; Suaidy, Sitti Evangeline Imelda (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2019)
Suicide among adolescent and early adulthood is an important public health issue. Among any cases of suicide attempt, suicide ideation is one of the strongest predictors that involved a death wish to think in detail about plans to commit suicide. This study was conducted to determine whether the psychological factors were influence on suicidal ideation among adolescents. In this study, loneliness, learning obstacle, activity other than learning, and gender has been seen as a factor that that will influence suicide ideation in adolescents. Subjects in this study were 259 students, taken with probability sampling techniques. CFA (Confirmatory Factor Analysis) was used to test the validity of Instrument and Multiple Regresion was used to test the hypotheses of the study. The result show that there is influence between loneliness, learning obstacle, activity other than learning, and gender on the suicide ideation in adolescent. Minor hypothesis test results show that bullying and loneliness had a significant effect on suicide ideation.